Jurnal Kata: ecocritical reunion of man and nature in the ruined cottage - bazregarzadeh, E. (Prodi Bahasa Inggris Fak sastra PETRA, 2015)
while the previous resarches on romanticism. especially wordsworth(1770-1850), and ecocriticism are quite far ranging